PENGARUH PENERAPAN SAP DAN SPIP TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA BOGOR DENGAN KOMPETENSI SDM SEBAGAI VARIABEL MODERATING - Setiawan, Ade Budi; Tami, Rizki Putra (Universitas Djuanda, 2018)
Local goverment financial statement in Bogor City for the last five years are still given fair opinion withthe exception by BPK. This research aims to determine effect of application Government AccountingStandards, and the Government Internal Control System on the quality of local goverment financialstatement in Bogor City with the Competence of Human Resources as moderating variable. The method ofthis research design is using survey methods with data collection method using questionnaires. Thepopulation in this research were employees in 39 financial administration officials in Regional Work unit(SKPD) of Bogor City, with using purposive sampling technique, so that the selected 195 employees thatthe research sample. The analysis technique used is MRA. The result of the analysis showed that simultantest or partial test, application of the Government Accounting Standards and Government Internal ControlSystem have significant impact on the quality of local government financial statement. The competence ofhuman resources as moderating variables can moderated the effect of the Government AccountingStandards and Government Internal Control System on the quality of local government financial statement.Coefficient of determination of 61,4 percent, while the rest 38,6 percent is explained by other variables.